THE EFFECT OF WORK FAMILY CONFLICT ON TURNOVER INTENTION MEDIATED BY WORK STRESS ON FEMALE EMPLOYEES OF BANK KALSEL(STUDY OF EMPLOYEES OF RANTAU AND KANDANGAN BRANCHES) - Dita Permatasari; Zakhyadi Ariffin (INJOSEDU: International Journal of Social and Education, 2025)
Female employees of Bank Kalsel who resign are closely related to work-family conflict. The increasing workload given by the company to employees can affect or trigger work stress. The approach of this research is quantitative. The population of the study was 32 female employees at Bank Kalsel, Rantau and Kandangan branches. Data collection used descriptive statistics and Structural Equation Modeling (SEM PLS) Path analysis. The results of the study showed: 1) Results of Descriptive Statistical Analysis of Variables with work-family conflict, turnover intention, and work stress variables consisting of 26 indicators, a total average of 3.68 (high), 3.73 (high), 3.91 ( high). 2) Results of PLS-SEM Data Analysis, namely (a) evaluation of the measurement model in the form of testing the validity and reliability of the research variables has a Cronbach's alpha and composite reliability value of more than 0.7 (has met reliability). (b) evaluation of the structural model in the form of testing the standardized root mean square residual (SRMR) value with a value of 0.089 (<0.1) (fit and feasible). The results of the hypothesis show that work family conflict has a positive influence on turnover intention, work family conflict has a positive influence on work stress, work stress has a positive influence on turnover intention, and work family conflict has a significant influence on turnover intention through the work stress variable.